Considering social values in the seafood sector using the Q-method. (February 2015) - MacDonald, Patricia A.; Murray, Grant; Patterson, Michele
Abstract: Ecosystem based ocean management processes seek to manage intricately linked social–ecological systems. These processes are intended to include and integrate appropriate economic, environmental, and social input into decision-making. To address identified challenges with gathering social data this study uses the Q-method to characterize different perspectives about what is valued about the ocean, seafood, and the community in the seafood sector of a single coastal community in British Columbia, Canada. Drawing on a sample of 42 people from the sector, this study identified a range of values, that group together into five distinct perspectives. These perspectives provide insight into how people value the experience versus the utility of the ocean and the different value they attribute to the outcomes of ocean management versus the process deployed. Values do not group together by seafood sub-sector, although the importance of teaching, stewardship, and conservation and respect for the ocean's resilience are common to all. On the other hand, the various perspectives most sharply diverge with respect to the role of aquaculture and special rights of access. This work demonstrates how the Q-method can help to identify, capture, and compare social values within a sector. In addition, this method can provide participants with a forum to discuss what is important and can provide a common vocabulary that cuts across existing constituencies. This has the potential to facilitate the consideration of a broad range of social values in ocean management. Highlights: An empirical illustration of value structures and value complexity. Provides evidence of common and divergent values within a defined coastal community. Has implications for understanding how people value all eco-system benefits and services. Shows Q-method as a practical tool to capture values and facilitate discussion. Demonstrates Q-method's potential to provide input to ocean management processes by creating common vocabulary and new groupings, and articulating points of disagreement and possibilities for dialogue.